Critical points of CSR‐related stakeholder dialogue in practice. (1st April 2014) - Golob, Ursa; Podnar, Klement
<x xml:space="preserve">Abstract</x> This paper examines the roles of dialogue in the process of communication with stakeholders. The conceptual frameworks of corporate social responsibility (CSR) and stakeholder relationships frequently present the initiation of a dialogue with stakeholders as a way for an organization to respond to criticisms of its social and environmental policies and actions. The paper discusses dialogue in the stakeholder and CSR literature. This is followed by the analysis of in‐depth semi‐structured interviews in the empirical section. Theoretical discussion and empirical examples demonstrate that the role of stakeholder dialogue in implementing CSR strategy is crucial in many ways. The case examples taken from the interviews with the heads of two large companies and two non‐governmental organizations illustrate the practical difficulties that may be encountered in applying the principle and practice of dialogue to the implementation of CSR programs in the real world.